1996
DOI: 10.1038/nm0996-985
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus–mediated wild–type P53 gene transfer to tumors of patients with lung cancer.

Abstract: A retroviral vector containing the wild-type p53 gene under control of a beta-actin promoter was produced to mediate transfer of wild-type p53 into human non-small cell lung cancers by direct injection. Nine patients whose conventional treatments failed were entered into the study. No clinically significant vector-related toxic effects were noted up to five months after treatment. In situ hybridization and DNA polymerase chain reaction showed vector-p53 sequences in posttreatment biopsies. Apoptosis (programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
301
1
6

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(310 citation statements)
references
References 26 publications
2
301
1
6
Order By: Relevance
“…[1][2][3][4][5][6][7][32][33][34] Additionally, in clinical trials, the restoration of wild-type p53 gene does not always lead to tumor regression or tumor growth inhibition. [8][9][10] Hence, there exists a need for identification of alternative candidates for effective gene therapy, in particular under conditions where p53 is ineffective. When p73 was identified, it was reported that p73 is not induced by DNA damage, 11 but later on it was found that p73 is indeed induced by a wide variety of DNA-damage-inducing drugs like adriamycin, etoposide, cisplatin, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][32][33][34] Additionally, in clinical trials, the restoration of wild-type p53 gene does not always lead to tumor regression or tumor growth inhibition. [8][9][10] Hence, there exists a need for identification of alternative candidates for effective gene therapy, in particular under conditions where p53 is ineffective. When p73 was identified, it was reported that p73 is not induced by DNA damage, 11 but later on it was found that p73 is indeed induced by a wide variety of DNA-damage-inducing drugs like adriamycin, etoposide, cisplatin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Moreover, in clinical trials the restoration of wild type p53 gene does not always lead to tumor regression or tumor growth inhibition suggesting resistance of some tumors to exogenous p53. [8][9][10] p73 is a member of p53 gene family and encodes proteins, which have significant homology with p53 both structurally and functionally. p73 can bind to p53 responsive elements and upregulate some of the p53 target genes suggesting that it has the potential for functional overlap with p53.…”
mentioning
confidence: 99%
“…Moreover, one might expect that p53 gene therapy would render targeted tumor cells capable of responding to chemotherapy by triggering p53-mediated cell growth arrest and apoptosis pathways. 5 To that end, we have performed gene therapy by introduction of an adenovirus genetically engineered to express wt p53 (rAd-p53) on eligible patients in a phase I clinical trial; in addition, a phase II trial was initiated in which patients received this therapy in association with complementary chemotherapy. A report on the clinical outcome of these patients (phase I) has already been published.…”
mentioning
confidence: 99%
“…29 Recent reports have indicated the successful transfer of wt p53 cDNA as suggested by increased apoptosis, using a retroviral vector, into the tumors of patients with lung cancer, although transgene expression was not actually detected. 16 In the present study, i.t. expression of vector-specific wt p53 RNA, as detected as by RT-PCR, was used as the primary endpoint.…”
Section: Discussionmentioning
confidence: 61%
“…[13][14][15] A recent study reported induction of apoptosis and tumor regression in patients with advanced NSCLC after injection of a retroviral vector containing wild-type (wt) p53 into tumors. 16 However, although vector sequences were detected in posttreatment biopsies by DNA polymerase chain reaction (PCR) or in situ hybridization, there was no demonstration of transgene expression. Intratumoral (i.t.)…”
mentioning
confidence: 99%